Reliable gold price predictor - Siti Roslindar, Yaziz; Roslinazairimah, Zakaria; Maizah Hura, Ahmad (2018)
The hybrid Box-Jenkins – GARCH (BJ-G) model has been shown to be a reliable model in forecasting gold price. A comprehensive algorithm using BJ-G model is proposed to forecast gold price. Daily world gold price is used in testing the forecasting performance of the proposed algorithm.